Self-employed door-to-door saleswomen: The obscure picture of potential entrepreneurs - Tayyaba Rafique Makhdoom (International Journal on Women Empowerment, 2015)
Optimization of all available human resources is required for sustainable economic development. Passive role of women is attributed to underdevelopment of countries including Pakistan. Entrepreneurship is one of the options for women that can contribute in their economic well-being, empowerment and ultimately benefit society at large. There is an obscure number of self-employed door-to-door saleswomen who identify and avail the opportunity by taking risk to purchase in bulk on credit or cash and peddle though not recognized as entrepreneurs. Personal interviews of 22 door-to-door saleswomen of Jamshoro District were conducted for data collection using purposive sampling. Majority of them buy from Hyderabad and few also approach Karachi, Punjab and abroad. Most of them purchase goods on cash and offer goods on credit or installment. Majority sales cloths and lingerie as they find a significant demand. Most of them are above 50, therefore counseling of their family members is required since old age women need care. Consistent to literature the education and number of dependents are found to be negatively related to self-employment because of uncertainty of income. ‘Convincing customers’, ‘mistrust of people’, ‘spoiled image’, ‘delay in payment and deception by customers’, ‘role conflict’, ‘harassment at houses’, ‘loss due to bulk buying’, and ‘high travel costs’ are few of the problems they mentioned. Convenient funding by government and NGOs are required. Inadequate record-keeping is blurring dealings and profit. Education will help them in adequate record-keeping and making rational decisions. Ethical practices are solution to clear their image and boost their morale.